Differential remodeling of extracellular matrices by breast cancer initiating cells. Issue 10 (19th January 2015) - Raja, Anju M.; Xu, Shuoyu; Zhuo, Shuangmu; Tai, Dean C.S.; Sun, Wanxin; So, Peter T.C.; Welsch, Roy E.; Chen, Chien‐Shing; Yu, Hanry
<x xml:space="preserve">Abstract</x> Cancer initiating cells (CICs) have been the focus of recent anti‐cancer therapies, exhibiting strong invasion capability via potentially enhanced ability to remodel extracellular matrices (ECM). We have identified CICs in a human breast cancer cell line, MX‐1, and developed a xenograft model in SCID mice. We investigated the CICs' matrix‐remodeling effects using Second Harmonic Generation (SHG) microscopy to identify potential phenotypic signatures of the CIC‐rich tumors. The isolated CICs exhibit higher proliferation, drug efflux and drug resistant properties in vitro; were more tumorigenic than non‐CICs, resulting in more and larger tumors in the xenograft model. The CIC‐rich tumors have less collagen in the tumor interior than in the CIC‐poor tumors supporting the idea that the CICs can remodel the collagen more effectively. The collagen fibers were preferentially aligned perpendicular to the CIC‐rich tumor boundary while parallel to the CIC‐poor tumor boundary suggesting more invasive behavior of the CIC‐rich tumors. These findings would provide potential translational values in quantifying and monitoring CIC‐rich tumors in future anti‐cancer therapies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> CIC‐rich tumors remodel the collagen matrix more than CIC‐poor tumors. </boxed-text>